The role of standarts in vegetable production - V.F. Pivovarov; L.V. Pavlov; O.T. Paraskova; V.M. Kononichina (Овощи России, 2012)
Standard is the main normative document regulating the important traits of seeds (germination ability, humidity, purity, regime of storage). This regulatory document provides the technological and economical basis for vegetable production and others features of agriculture.